Surface Analysis of Native Spider Draglines by FE-SEM and XPS - Sogawa, Hiromitsu; Nakano, Kyohei; Tateishi, Ayaka; Tajima, Keisuke; Numata, Keiji (Frontiers in Bioengineering and Biotechnology, 2020)
Although the physical and biological functions of the skin layer of spider dragline have been studied and partially clarified, the morphology and elemental contents of the skin layer of silk fibers have not been investigated in detail to date. Here, the surface of Nephila clavata spider dragline was evaluated by field emission scanning electron microscopy (FE-SEM) and X-ray photoelectron spectroscopy (XPS) to obtain clear surface morphological and molecular information. The FE-SEM images of the spider dragline indicate that the spider dragline forms a bundle of microfibrils. This hierarchical structure might induce faint fibrilar and network-like patterns on the surface of the dragline. XPS analysis revealed the presence of Na, P, and S, which are reasonably explained by considering the biological components of the major ampullate gland of spiders. The results obtained here are preliminary but will be important to consider the molecular transition of silk proteins to form excellent hierarchical structures during the spider dragline spinning process.